2021
DOI: 10.3390/jcm10153266
|View full text |Cite
|
Sign up to set email alerts
|

Association between Objectively Measured Physical Activity and Arterial Stiffness in Children with Congenital Heart Disease

Abstract: Background: The association between physical activity (PA) and arterial stiffness is particularly important in children with congenital heart disease (CHD) who are at risk for arterial stiffening. The aim of this study was to examine the association between objectively measured PA and arterial stiffness in children and adolescents with CHD. Methods: In 387 children and adolescents with various CHD (12.2 ± 3.3 years; 162 girls) moderate-to-vigorous PA (MVPA) was assessed with the “Garmin vivofit jr.” for 7 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Similarly in various types of congenital heart disease, increased arterial stiffness has been reported. ( Müller et al, 2015 ; Häcker et al, 2018 ; Sandhu et al, 2021 ; Willinger et al, 2021 ). For patients with repaired CoA, there have been some reports on increased cfPWV.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in various types of congenital heart disease, increased arterial stiffness has been reported. ( Müller et al, 2015 ; Häcker et al, 2018 ; Sandhu et al, 2021 ; Willinger et al, 2021 ). For patients with repaired CoA, there have been some reports on increased cfPWV.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relationship between optimal physical activity levels and arterial stiffness is controversial, with studies suggesting a negative association, 6 ) whereas others have reported no significant association. 7 )…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it remains unclear that repeated acute exercise-induced functional change could result in a chronic structural effect; in other words, it is unknown how the repeated acute effect of exercise improves arteriosclerosis. Another interesting study [10] examined the effect of objectively measured physical activity on arterial stiffness in children and adolescents with congenital heart disease. However, the authors did not find an effect of physical activity on arterial stiffness in children with cardiovascular disease, and they concluded that these results may have been due to low activity or short exposure to the respective risk factors, as the patients were children.…”
mentioning
confidence: 99%